Does corporate social responsibility affect the performance of firms? - Sergio Vergalli; Laura Poddi (Fondazione Eni Enrico Mattei (FEEM), 2009)
Over the last two decades in OECD countries increasingly more firms are certifying as Socially Responsible (CSR is the acronym for Corporate Social Responsibility). This kind of certification is assigned by private companies that guarantee that a certain firm's behaviour is environmentally and sociologically correct. Some papers (including Preston and O'Bannon, 1997; Waddock and Graves, 1997; McWilliams and Sieger, 2001; Ullman, 1985) tried to establish if there exists a link between Social Responsibility certification and the performance of firms. Their results were ambiguous and did not show any common connection. This ambiguity depends mainly on the static nature of their analyses and on the problem of whether performance is affected more by certification costs or by increasing sales due to an effect on reputation. Our work would like to discover whether certain performance indicators are affected by a firm's social responsible behaviour and their certifications by looking at panel data. The novelty of our analysis is due to its dynamic aspect and from a CSR index that intersects two of the three main international indices (Domini 400 Social Index, Dow Jones Sustainability World Index, FTSE4Good Index), to be objective and obtain a representative sample. The main results seem to support the idea that CSR firms which are more virtuous, have better long run performance. They have some initial costs but obtain higher sales and profits due to several causes reputation effect, a reduction of long run costs and increased social responsible demand.
Keywords: M14; C23; O10; 330; Corporate Social Responsibility; Growth